2015
DOI: 10.1016/s1995-7645(14)60326-6
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of EGFR gene mutation with pathological features and prognosis in patients with non–small–cell lung carcinoma

Abstract: EGFR gene mutation has significant relevance with pathological features, the prognosis of EGFR-mutant-patients is better than that of EGFR- wide type-patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Another study revealed a significant relationship between blood type and EGFR mutation; however, the investigators did not mention the specific blood type, and analyses were secondary. 22 Also, EGFR mutation was not associated with smoking history in this study. The current case-control study included only lung adenocarcinoma patients with the main objective to evaluate blood type as a predictive factor for EGFR mutation status.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Another study revealed a significant relationship between blood type and EGFR mutation; however, the investigators did not mention the specific blood type, and analyses were secondary. 22 Also, EGFR mutation was not associated with smoking history in this study. The current case-control study included only lung adenocarcinoma patients with the main objective to evaluate blood type as a predictive factor for EGFR mutation status.…”
Section: Discussionmentioning
confidence: 43%
“…[12][13][14][15][16][17][18][19][20] However, to our knowledge, only two studies have investigated the relationship between blood type and EGFR mutation in lung cancer, and thus it remains poorly investigated. 21,22 The study aims to evaluate the relationship between blood type and EGFR mutation positivity in lung adenocarcinoma patients.…”
mentioning
confidence: 99%